1991
DOI: 10.1107/s0108270191004031
|View full text |Cite
|
Sign up to set email alerts
|

Structure of 4,7-didehydroneophysalin B, acid-induced rearrangement product of physalin A

Abstract: Abstract. C28H2809,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…[9][10][11][12][13] The unusual steroids and variety of biological activities of this plant prompted us to extend our studies to the calyces of P. alkekengi var. franchetii, which resulted in the isolation of 15 physalins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and eight flavonoids (16)(17)(18)(19)(20)(21)(22)(23). This paper describes the structural elucidation of four new physalins (1, 2, 6, 7) and the inhibitory effect of the isolated compounds on NO production in LPS-activated macrophages.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] The unusual steroids and variety of biological activities of this plant prompted us to extend our studies to the calyces of P. alkekengi var. franchetii, which resulted in the isolation of 15 physalins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and eight flavonoids (16)(17)(18)(19)(20)(21)(22)(23). This paper describes the structural elucidation of four new physalins (1, 2, 6, 7) and the inhibitory effect of the isolated compounds on NO production in LPS-activated macrophages.…”
mentioning
confidence: 99%
“…The Csp 3 -Csp 3 bond distances lie in the range 1.508 (3)-1.566 (2) Å . The C24-C25-C26 [117.03 (15) ], C9-C11-C12 [119.48 (14) ] and C11-C12- C13 [119.98 (14) ] angles deviate significantly from ideal tetrahedral values, as reported for this class of compounds (Kawai et al, 1970(Kawai et al, , 1994Taga et al, 1991). The bond angles involving the spiro atom C17 range from 102.02 (13) to 115.05 (13) .…”
Section: Commentmentioning
confidence: 68%
“…The two epoxy seven-and eight-membered rings (O7/C14-C16/C24/C25/C27 and C8/C9/C11-C14/C17/O8) are in chair and boat-chair conformations, respectively. The Csp 3 -Csp 3 bond distances lie in the range 1.508 3 (Kawai et al, 1970(Kawai et al, , 1994Taga et al, 1991). The bond angles involving the spiro atom C17 range from 102.02 13 together by these interactions to form a three-dimensional molecular network (Fig.…”
Section: Data Collectionmentioning
confidence: 99%
“…Reference to Taga et al . () and Matsuura et al . () showed that physalin A could be transformed to 4,7‐didehydroneophysalin B (C 28 H 28 O 9 ), anhydrophysalin A (C 28 H 28 O 9 ) and dehydrophysalin B (C 28 H 28 O 9 ) under acid conditions, so we can conclude that 4,7‐didehydroneophysalin B could transform to anhydrophysalin A and dehydrophysalin B through a rearrangement reaction.…”
Section: Resultsmentioning
confidence: 87%